Prevalence of vitamin D deficiency among diagnosed cases of asthma and its correlation with duration, gender, and socioeconomic aspects - Sara Bano; Hafiza Faiza Rauf; Shazia Shakoor; Aasia Ismail; Fahad Usman; Sadia Rehman (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Vitamin D deficiency has been increasingly implicated in the pathophysiology of asthma, with evidence suggesting its potential role in disease severity, duration, and response to therapy. To determine vitamin D deficiency among diagnosed cases of asthma and its correlation with duration of asthma, gender, and socioeconomic aspects.METHODOLOGY: This study employed an analytical cross-sectional design. The study was conducted at Imran Idrees Hospital, affiliated with Sialkot Medical College, Sialkot. A sample of 200 asthmatic patients, aged 18 to 60, was included. Patients who were both male and female, and had a clinical diagnosis of asthma verified by spirometry for a minimum of six months, satisfied the inclusion criteria. Patients with asthma-COPD overlap, pregnancy, chronic systemic disorders, or recent vitamin D supplement use (last six months) were excluded. The data were analyzed using SPSS version 23.RESULTS: Bivariate analysis was done to compare the sociodemographic profile and duration of asthma on vitamin D levels. The proportion of individuals with low vitamin D levels was higher in those who had asthma for more than 30 years. The female gender had a significantly higher proportion of low vitamin D as compared to males.  CONCLUSION: The study revealed that the duration of asthma and gender were significantly associated with vitamin D levels among patients with asthma. Individuals with longer asthma duration and females were found to have low vitamin D levels.